Magnetic powder core and preparation method thereof

By annealing the nanocrystal powder and mixing with the binder, and heating treatment to obtain a magnetic powder core, the problem of large loss of nanocrystal material magnetic powder core is solved, and the effect of improving magnetic permeability and reducing losses is achieved.

CN119446765APending Publication Date: 2025-02-14HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411713958.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The magnetic powder cores prepared by existing nanocrystalline materials have a large loss and need to overcome this defect.

Method used

By annealing the nanocrystal powder in a protective atmosphere, the annealing temperature is controlled at 580-610°C, then mixed with the binder and pressed into a blank, and then heated to obtain a magnetic powder core. The method also adds a coupling agent and a modified silicone resin containing epoxy groups as the binder.

Benefits of technology

The magnetic permeability of the magnetic powder core is improved, while the loss of the magnetic powder core is reduced. The preparation method is low in cost and simple in process, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156452840000071
    Figure BDA0005156452840000071
  • Figure BDA0005156452840000081
    Figure BDA0005156452840000081
  • Figure BDA0005156452840000091
    Figure BDA0005156452840000091
Patent Text Reader

Abstract

The invention discloses a magnetic powder core and a preparation method thereof, belongs to the technical field of magnetic powder cores, and overcomes the defect that in the prior art, a magnetic powder core prepared from a nanocrystalline material is large in loss. The preparation method of the magnetic powder core comprises the following steps that S1, nanocrystalline powder is subjected to annealing treatment in a protective atmosphere, and the annealing treatment temperature ranges from 580 DEG C to 610 DEG C; s2, the nanocrystalline powder obtained after annealing treatment is mixed with a binder, and then the mixture is pressed into a blank; and S3, the blank is heated, and the magnetic powder core is prepared. According to the method, the magnetic conductivity of the magnetic powder core can be improved, and meanwhile the loss of the magnetic powder core is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic powder cores, and in particular relates to a magnetic powder core and a preparation method thereof. Background Art

[0002] Nanocrystalline material is a kind of magnetic powder core material, which is widely used in transformers, inductors, electronics, medicine and other fields. Compared with traditional crystalline magnetic powder core materials, magnetic powder cores made of nanocrystalline materials have many advantages such as higher magnetic permeability, higher saturation strength, better high temperature resistance, lower loss, etc. These characteristics can significantly improve the energy efficiency of transformers, reduce the power loss of inductors and motors, improve their efficiency, maintain stable magnetic permeability in high temperature environments, improve computer performance, and improve the accuracy of magnetic resonance imaging systems.

[0003] However, the magnetic powder cores made from existing nanocrystalline materials suffer from high losses. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of large loss of magnetic powder cores prepared from nanocrystalline materials in the prior art, thereby providing a magnetic powder core and a preparation method thereof.

[0005] To this end, the present invention provides the following technical solutions.

[0006] In a first aspect, the present invention provides a method for preparing a magnetic powder core, comprising the following steps:

[0007] S1, annealing the nanocrystalline powder in a protective atmosphere at a temperature of 580-610°C;

[0008] S2, mixing the annealed nanocrystalline powder with a binder, and then pressing it into a blank;

[0009] S3, heat-treating the blank to obtain a magnetic powder core.

[0010] In a possible embodiment, S2 further comprises adding a coupling agent;

[0011] Preferably, the amount of the coupling agent added is 0.3% to 0.7% of the mass of the nanocrystalline powder, more preferably 0.4% to 0.6%;

[0012] Preferably, the amount of the binder added is 0.5% to 2.5%, preferably 1% to 2%, of the total mass of the nanocrystalline powder and the coupling agent, so as to avoid the phenomenon of delamination and powder loss caused by too little binder, or the phenomenon of adhesion to the mold during pressing and ring removal caused by too much binder.

[0013] In one possible embodiment, the coupling agent includes methyltrimethoxysilane and isopropyl trioleyl titanate;

[0014] Preferably, the mass ratio of methyltrimethoxysilane to isopropyltrioleyl titanate is (0.9-1.1):(0.9-1.1).

[0015] In a possible implementation, the binder is a modified silicone resin containing epoxy groups.

[0016] In a possible implementation, the method for preparing the modified silicone resin includes: reacting silicone resin with epoxy resin under the action of a catalyst;

[0017] Preferably, the mass ratio of the silicone resin to the epoxy resin is (0.5-1.5):(0.5-1.5);

[0018] Preferably, the catalyst comprises one or more of titanium acetylacetonate and titanium chloride;

[0019] Preferably, the reaction temperature is 50-200°C and the reaction time is 1-20h;

[0020] Preferably, the silicone resin includes one or more of methyl silicone resin, methylphenyl silicone resin, and amino silicone resin;

[0021] Preferably, the epoxy resin is one or more of bisphenol A epoxy resin and novolac epoxy resin.

[0022] In a possible implementation, S2 includes:

[0023] S201, mixing a coupling agent and a first solvent, then adding the annealed nanocrystalline powder, stirring and removing the first solvent;

[0024] S202, mixing the binder with the second solvent, then adding the product of S201, stirring and removing the second solvent;

[0025] S203, pressing the product of S202 into a blank.

[0026] In a possible implementation, at least one of the following conditions is met:

[0027] (1) The first solvent is an organic solvent. Preferably, the first solvent includes one or more of anhydrous ethanol, ethylene glycol and propanol;

[0028] (2) The second solvent is an organic solvent. Preferably, the second solvent includes one or more of acetone, toluene and xylene;

[0029] (3) The pressing pressure is 500 to 2000 MPa.

[0030] In a possible implementation manner, S1 satisfies at least one of the following conditions:

[0031] (1) The protective atmosphere includes one or more of N2, Ar and He;

[0032] (2) The annealing temperature is 590-600°C;

[0033] (3) The heating rate of the annealing treatment is 1 to 5°C / min;

[0034] (4) The holding time of annealing treatment is 1 to 4 hours;

[0035] (5) The general formula of the nanocrystalline powder is Fe a Si b Nb c B d Cu e , where a is 66-89, b is 4-12, c is 6-16, d is 0.5-3.5, and e is 0.5-2.5. a%, b%, c%, d%, and e% are the mass percentages of Fe, Si, Nb, B, and Cu in the nanocrystalline powder, respectively.

[0036] In a possible implementation manner, S3 satisfies at least one of the following conditions:

[0037] (1) The temperature of the heating treatment is 140 to 200°C;

[0038] (2) The heating rate of the heating treatment is 1 to 4°C / min;

[0039] (3) The holding time of the heating treatment is 1 to 4 hours;

[0040] (4) The heating treatment is carried out in a protective atmosphere.

[0041] In a second aspect, the present invention provides a magnetic powder core produced by the preparation method.

[0042] The technical solution of the present invention has the following advantages:

[0043] 1. The preparation method of the magnetic powder core of the present invention comprises the following steps: S1, annealing the nanocrystalline powder in a protective atmosphere at a temperature of 580-610°C; S2, mixing the annealed nanocrystalline powder with a binder, and then pressing it into a blank; S3, heating the blank to obtain a magnetic powder core.

[0044] The present invention performs preliminary annealing on the nanocrystalline powder, which can reduce the size of the crystal grains and have a higher surface-to-volume ratio, thereby reducing the hysteresis loss of the nanocrystalline powder under the premise of improving the magnetic permeability; the temperature of the annealing treatment is 580-610°C, when the annealing temperature is too low, the crystal grains cannot be fully grown and crystallized, and when the annealing temperature is too high, the crystal grains will grow abnormally, so the annealing temperature needs to be controlled within the range of the present invention, so that the performance of the nanocrystalline material can achieve an ideal effect, thereby improving the magnetic permeability of the magnetic powder core and reducing the loss of the magnetic powder core.

[0045] The present invention reduces loss while improving magnetic permeability, and the preparation method has low cost, adopts a simple process, and is suitable for industrial production.

[0046] 2. S2 also includes the addition of a coupling agent; the coupling agent includes methyltrimethoxysilane and isopropyltrioleyl titanate. The coupling agent is a mixture of methyltrimethoxysilane and isopropyltrioleyl titanate. The methyltrimethoxysilane molecule contains an organic group, which is more suitable for improving the compatibility of the surface of the components and increasing the adhesion, while the isopropyltrioleyl titanate has a thicker covering layer on the surface of the material, improving the bonding ability and increasing the mutual adhesion of the interface. Methyltrimethoxysilane and isopropyltrioleyl titanate can complement each other when processing nanocrystalline materials to produce a synergistic effect, thereby improving the coupling effect, further improving the magnetic permeability of the nanocrystalline material, and reducing the loss of the nanocrystalline material.

[0047] 3. The binder is a modified silicone resin containing epoxy groups. The epoxy groups can enhance the chemical bonding ability of the resin, thereby enhancing the bonding force with the nanocrystalline material, dispersing the particles of the nanocrystalline material, improving the uniformity of the particles, increasing the density, and thus improving the magnetic permeability. DETAILED DESCRIPTION

[0048] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0049] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0050] Example 1

[0051] This embodiment provides a method for preparing a magnetic powder core, comprising the following steps:

[0052] (1) Nanocrystalline powder Fe 81.5 Si 8.5 Nb 7.5 B 1.5 Cu1 was annealed at a heating rate of 3°C / min, a holding temperature of 600°C, a holding time of 2h, and nitrogen protection throughout the process.

[0053] (2) Dissolve the coupling agent in anhydrous ethanol, add the annealed nanocrystalline powder, stir until the anhydrous ethanol is completely volatilized, and pass through a 120-mesh sieve. The weight of the coupling agent is 0.5% of the weight of the nanocrystalline powder, and the coupling agent is a mixture of methyltrimethoxysilane and isopropyltrioleyl titanate, and the mass ratio of the two is 1:1.

[0054] (3) Dissolve the binder in acetone, add the product of step (2), stir until the acetone is completely volatilized, and pass through a 40-mesh sieve. The binder is 1.5% of the mass of the product of step (2).

[0055] The adhesive in this embodiment is a silicone resin containing epoxy groups, and the preparation method includes: mixing silicone resin (methyl silicone resin, Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd.-5201P) and epoxy resin (bisphenol A type epoxy resin, McLean) in a mass ratio of 1:1, adding a catalyst (titanium acetylacetonate, McLean) of 0.3% by mass of the silicone resin, and reacting at 60°C for 5 hours to obtain the adhesive.

[0056] (4) The product of (3) is pressed into a ring-shaped billet at a pressing pressure of 800 MPa.

[0057] (5) The blank was subjected to a heating treatment, the heating rate of the heating treatment was 2°C / min, the holding temperature of the heating treatment was 160°C, the holding time of the heating treatment was 2h, and nitrogen protection was used throughout the process.

[0058] Example 2

[0059] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the holding temperature of the annealing treatment is 580°C.

[0060] Example 3

[0061] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the holding temperature of the annealing treatment is 590°C.

[0062] Example 4

[0063] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the holding temperature of the annealing treatment is 610°C.

[0064] Comparative Example 1

[0065] This comparative example provides a method for preparing a magnetic powder core, which is basically the same as Example 1, except that step (1) is not included, that is, the nanocrystalline powder is not annealed.

[0066] The density of the magnetic powder cores obtained in the embodiments and comparative examples was calculated, and the magnetic permeability at 100kHz / 1V and the loss at 1MHz / 200mT were tested. The results are shown in Table 1.

[0067] Table 1

[0068]

[0069] As can be seen from Table 1, the magnetic permeability of the magnetic powder core prepared by the present invention is significantly improved, the loss is significantly reduced, and the density is also improved to a certain extent. When the annealing and holding temperature is between 590 and 600°C, the improvement of the magnetic permeability and the reduction of the loss are more obvious.

[0070] Example 5

[0071] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the weight of the coupling agent is 0.3% of the weight of the nanocrystalline powder.

[0072] Example 6

[0073] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the weight of the coupling agent is 0.4% of the weight of the nanocrystalline powder.

[0074] Example 7

[0075] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the weight of the coupling agent is 0.6% of the weight of the nanocrystalline powder.

[0076] Example 8

[0077] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the weight of the coupling agent is 0.7% of the weight of the nanocrystalline powder.

[0078] Example 9

[0079] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that no coupling agent is added.

[0080] Example 10

[0081] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the coupling agent is methyltrimethoxysilane.

[0082] Embodiment 11

[0083] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the coupling agent is isopropyl trioleyl titanate.

[0084] Table 2

[0085]

[0086] It can be seen from Table 2 that adding a coupling agent can further improve the magnetic permeability of the magnetic powder core and further reduce the loss, and a better effect can be obtained when the amount of coupling agent added is in the range of 0.4% to 0.6%. A better effect can be obtained when a mixture of methyltrimethoxysilane and isopropyltrioleyl titanate is used as a coupling agent.

[0087] Example 12

[0088] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the amount of binder added is 0.5%.

[0089] Embodiment 13

[0090] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the amount of binder added is 1%.

[0091] Embodiment 14

[0092] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the amount of binder added is 2%.

[0093] Embodiment 15

[0094] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the amount of binder added is 2.5%.

[0095] Example 16

[0096] This embodiment provides a method for preparing a magnetic powder core, which is basically the same as that of Embodiment 1, except that the binder of this embodiment is silicone resin (methyl silicone resin, Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd.-5201P) that is not modified with epoxy resin.

[0097] Table 3

[0098]

[0099]

[0100] It can be seen from Table 3 that better effects can be obtained when the amount of binder added is in the range of 1% to 2%, and better effects can be obtained when silicone resin modified with epoxy groups is used as the binder.

[0101] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a magnetic powder core, characterized in that: The following steps are involved: S1, annealing the nanocrystalline powder in a protective atmosphere at a temperature of 580-610°C; S2, mixing the annealed nanocrystalline powder with a binder, and then pressing it into a blank; S3, heat-treating the blank to obtain a magnetic powder core.

2. The method for preparing a magnetic powder core according to claim 1, characterized in that: The S2 further comprises adding a coupling agent; Preferably, the amount of the coupling agent added is 0.3% to 0.7% of the mass of the nanocrystalline powder, more preferably 0.4% to 0.6%; Preferably, the amount of the binder added is 0.5% to 2.5% of the total mass of the nanocrystalline powder and the coupling agent, preferably 1% to 2%.

3. The method for preparing a magnetic powder core according to claim 2, characterized in that: Coupling agents include methyltrimethoxysilane and isopropyltrioleyl titanate; Preferably, the mass ratio of methyltrimethoxysilane to isopropyltrioleyl titanate is (0.9-1.1):(0.9-1.1).

4. The method for preparing a magnetic powder core according to claim 2, characterized in that: The adhesive is a modified silicone resin containing epoxy groups.

5. The method for preparing a magnetic powder core according to claim 4, characterized in that: The preparation method of the modified silicone resin comprises: silicone resin and epoxy resin react under the action of a catalyst; Preferably, the mass ratio of the silicone resin to the epoxy resin is (0.5-1.5):(0.5-1.5); Preferably, the catalyst comprises one or more of titanium acetylacetonate and titanium chloride; Preferably, the reaction temperature is 50-200°C and the reaction time is 1-20h; Preferably, the silicone resin includes one or more of methyl silicone resin, methylphenyl silicone resin, and amino silicone resin; Preferably, the epoxy resin is one or more of bisphenol A epoxy resin and novolac epoxy resin.

6. The method for preparing a magnetic powder core according to claim 2, characterized in that S2 include: S201, mixing a coupling agent and a first solvent, then adding the annealed nanocrystalline powder, stirring and removing the first solvent; S202, mixing the binder with the second solvent, then adding the product of S201, stirring and removing the second solvent; S203, pressing the product of S202 into a blank.

7. The method for preparing a magnetic powder core according to claim 6, characterized in that: At least one of the following conditions is met: (1) The first solvent is an organic solvent. Preferably, the first solvent includes one or more of anhydrous ethanol, ethylene glycol and propanol; (2) The second solvent is an organic solvent. Preferably, the second solvent includes one or more of acetone, toluene and xylene; (3) The pressing pressure is 500 to 2000 MPa.

8. The method for preparing a magnetic powder core according to any one of claims 1 to 7, characterized in that: S1 satisfies at least one of the following conditions: (1) The protective atmosphere includes one or more of N2, Ar and He; (2) The annealing temperature is 590-600°C; (3) The heating rate of the annealing treatment is 1 to 5°C / min; (4) The holding time of annealing treatment is 1 to 4 hours; (5) The general formula of the nanocrystalline powder is Fe a Si b Nb c B d Cu e , where a is 66-89, b is 4-12, c is 6-16, d is 0.5-3.5, and e is 0.5-2.

5.

9. The method for preparing a magnetic powder core according to any one of claims 1 to 7, characterized in that: S3 meets at least one of the following conditions: (1) The temperature of the heating treatment is 140 to 200°C; (2) The heating rate of the heating treatment is 1 to 4°C / min; (3) The holding time of the heating treatment is 1 to 4 hours; (4) The heating treatment is carried out in a protective atmosphere.

10. A magnetic powder core obtained according to the preparation method according to any one of claims 1 to 9.